ACCUMULATION OF HEAVY METALS PB, CU, AND ZN IN THE MANGROVE FOREST OF MUARA ANGKE, NORTH JAKARTA - Faisal Hamzah (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2010)
In this study, the concentrations of three kinds of heavy metals, namely Pb, Zn, and Cu from 3 species of mangrove that grow in Muara Angke were measured and analyzed. Our result showed that substrate of mangrove ecosystem in Muara Angke was dominated by clay (30.5% - 62.4%), silt (21.7% -35.6%), and sand (2% -39.5%). The heavy metals accumulation in roots is higher than in sediment, water and leaves with concentration of Zn as the highest. Bioconcentration Factor (BCF; content ratio of heavy metal concentrations in roots or leaves and sediment) and Translocation Factor (TF; ratio of heavy metal concentrations in leaves and roots) of non-essential heavy metals (Pb) is higher in leaves than in roots, but for essential heavy metals (Zn and Cu), the BCF and TF was higher in roots than in leaves. TF values for heavy metals Pb, Cu, and Zn were 0.98-2.59, 0.17-0.51, and 0.52-0.86, respectively. The values of root BCF of those three heavy metals were 0.71-3.17, 0.27-0.74, and 0.95-1.53, while the values of leaf BCF were 1.84-3.45, 0.07-0.34, and 0.72-1.19, respectively. Furthermore, by calculating the phytoremediation (FTD), i.e. the difference between BCF and TF, it is obtained that Sonneratia caseolaris and Avicennia marina can be used in phytoremidiation, with leaves and roots FTD of 1.93 and 2.09, respectively for Sonneratia caseolaris and 1.93 and 1.98 for Avicennia marina.Keywords: heavy metals, mangroves, phytoremidiation, Muara Angke, bioconcentration factor, translocation factor